QUANTITATIVE ASSESSMENT OF POPULATIONS, SUBPOPULATIONS OF LYMPHOCYTES AND PHAGOCYTIC CELLS IN HIV-PATIENTS - N.V. Ilenko; T.A. Petrushanko; N.N. Ilenko (Український стоматологічний альманах)
The epidemiological situation in Ukraine on HIV / AIDS has become worse. That is why a profound and detailed study of all aspects of HIV infection is extremely important.